2015
DOI: 10.5964/ejop.v11i1.829
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Development in Adolescence and Early Adulthood: The Growing Complexity of Recursive Thinking Ability

Abstract: This study explores the development of theory of mind, operationalized as recursive thinking ability, from adolescence to early adulthood (N = 110; young adolescents = 47; adolescents = 43; young adults = 20). The construct of theory of mind has been operationalized in two different ways: as the ability to recognize the correct mental state of a character, and as the ability to attribute the correct mental state in order to predict the character’s behaviour. The Imposing Memory Task, with five recursive thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
63
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 37 publications
4
63
1
1
Order By: Relevance
“…Infants already possess ‘implicit’ mindreading capacities (Slaughter, 2015), treating themselves and others as intentional agents and experiencers; while older children understand lies and deception (Peterson and Siegal, 2002). Research shows that ToM development even prolongs into late adolescence (Dumontheil et al, 2010; Vetter et al, 2013; Valle et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Infants already possess ‘implicit’ mindreading capacities (Slaughter, 2015), treating themselves and others as intentional agents and experiencers; while older children understand lies and deception (Peterson and Siegal, 2002). Research shows that ToM development even prolongs into late adolescence (Dumontheil et al, 2010; Vetter et al, 2013; Valle et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Teachers in the experimental condition were trained on how to promote mentalizing skills through the adoption of everyday school teaching strategies and were then left free to propose to their pupils these activities when and how they preferred. Findings showed that only children in the experimental group improved their performance on third‐order false‐belief understanding (Valle, Massaro, Castelli, & Marchetti, ) and on two subcomponents of the Mentalizing task (Sharp, Croudace, & Goodyer, ). Overall, then, this study showed that even if teachers were not instructed to follow detailed scripts and procedures, they are able to successfully promote their pupils' mind‐reading.…”
Section: Introductionmentioning
confidence: 99%
“…Theory of mind develops during childhood and continues to evolve in adolescence (Valle et al, 2015) and adulthood (Apperly et al, 2009; Sommerville et al, 2013). According to a socio-constructivist approach, theory of mind emerges within contexts of social interactions, thanks to the participation in social exchanges (Astington and Olson, 1995; Carpendale and Lewis, 2004).…”
Section: Introductionmentioning
confidence: 99%